Pengaruh Lingkungan Keluarga dan Lingkungan Sekolah Terhadap Hasil Belajar Mata Pelajaran Ekonomi Siswa Kelas XII IPS SMAN 11 Kabupaten Tebo - Indriana, Risma; Kasiono, Kasiono (SJEE (Scientific Journals of Economic Education), 2025)
This research aims to determine the influence of the family environment and school environment on learning outcomes in the Economics Subject Class XII IPS at SMAN 11 Tebo Regency. The research method used in this research is a quantitative method using multiple linear regression analysis techniques. The results of the research show that there is a significant influence between the family environment and the school environment simultaneously on student learning outcomes in economics subjects at SMAN 11 Tebo Regency. This is shown by the value of fcount > ftable, namely 3.691 > 2.77. So, this implies that a good family environment will support a stable foundation for students. So the family environment has an important role in shaping student learning outcomes. Meanwhile, the existence of a school environment with a conducive atmosphere, good facilities and infrastructure will be able to make students more active in their studies so that their learning outcomes will improve.